Aldol Condensations of Aldehydes and Ketones Catalyzed by Primary Amine on Water - Zhang, Xu; Xiong, Yan; Zhang, Shuting; Ling, Xuege; Wang, Jinyue; Chen, Changguo (Asian Journal of Chemistry, 2011)
Potassium glycinate-catalyzed aldol condensation reactions of aromatic aldehydes and ketones on water at room temperature have been developed. Under optimal conditions, various condensation adducts are furnished in up to 63 % yield. By simple separation of the oil phase, potassium glycinate-containing water is reused to catalyze aldol condensation for six runs without loss of catalytic activity. Theoretical investigation reveals correlation between the yields and dehydroxylation energy barriers of aldol products, reasonably low activation energy of 11.9 kcal/mol for transition state formation in condensation of benzaldehyde and acetone, vibrations between aldol donor and acceptor, which correspond to the only imaginary frequency (-179.8i).